CLASSROOM MANAGEMENT : ITS ROLE IN SCHOOL VIOLENCE PREVENTION - E. Hanse, Aldila (MAGISTRA, 2012)
This article reviews the role of classroom management in preventing the trending cases of school violence by highlighting theoretical frameworks essential for teachers in selecting and defending certain model of classroom management. Based on the review, it provides a number of effective classroom management strategies in preventing school violence. It also discusses the advantages and disadvantages of democracy in classroom as well as the importance of teacher training, both theory and practice, in rising teachersâ awareness of potentially violence situation along with safe and effective techniques to manage aggressive students.